PENGARUH INOVASI PRODUK, KUALITAS PRODUK, DAN EKUITAS MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA KECIL MENENGAH ALAT PERAGA EDUKATIF CHILDREN TOY’S DI KABUPATEN SEMARANG - Yulianingrum Iga Widhianti; Wahyu Hidayat; Agung Budiatmo (Jurnal Ilmu Administrasi Bisnis, 2013)
This study aimed to to determine the effect variables of Product Innovation, Product Quality and Brand Equity on Purchase Decision  On Small and Medium Enterprises Educative Props Children Toy’s in Semarang District. This type of research used is explanatory research, data collection methods using an  interview and  questionnaire with a sample of 100 respondents who make a purchase on  Small and Medium Enterprises Educative Props Children Toy’s via nonprobability sampling technique by using purposive sampling method. The results of the statistical linear regression analysis can be shown by the regression equation Y = - 1.466+ 0,562X1 + 0,481X2+ 0,109X3 e. From the regression equation it is known that the product innovation, product quality and brand equity has an effect on purchase decision. The results of the calculation of the coefficient of determination 0.725 magnitude. It is indicating that the product innovation, product quality and brand equity variables could explain 72,5% of purchase decision. Based on the results of the data analysis we can conclude the existence effect of product innovation, product quality and brand equity to purchase decision Educative Props Children Toy’s and have a strong level of closeness relationship this means that the higher product innovation, product quality and brand equity that will lead to the higher purchase decision. Companies can improve product innovation by adjusting the needs of consumers, improve the quality of packaging products mainly deals with products that are still moldy so much attention at the time of packaging, improve brand equity by creating the web to introduce more products and brands, and need a guidebook  for any desain product.